Antonio Banderas: Hispanic Gay Masculinities and the Global Mirror Stage (1991-2001) - Joseba Gabilondo (Studies in 20th & 21st Century Literature, 2006)
Here I map out the Atlantic intertwining between neo-liberal/neo-imperial Spain and cinema by analyzing Antonio Banderas's body politics as the postmodern (post- or neoimperialist) Don Juan. Banderas's career trajectory from 1991 to 2001 coincides with larger political and historical developments. He arrived in Hollywood in the early 1990s, a moment when different but interconnected historical events came together— the end of the Cold War and the neo-liberal globalization of the United States with treaties such as NAFTA and GATT; the growing public profile of the fundamentalist religious right and gays; and the mainstream population's (unwilling) acceptance of Latinos as a differentiated community. Hollywood needed a new kind of masculinity that gathered in all these new dimensions of United States identity while not completely shedding traditional Hollywood male typology, and Banderas fulfilled all the requirements. At the same time in Banderas Spain acquired a global card of presentation for its new neoimperialist and Atlantic pursuits in Latin America.
Keywords: Antonio Banderas; Hispanic gay masculinities; gay masculinity; masculinity; Atlantic; neo-liberal; Spain; cinema; Spanish cinema; neoimperialist; postmodern; Don Juan; body politics; Hollywood; male typology